Ant diversity decreases during the dry season: A meta‐analysis of the effects of seasonality on ant richness and abundance. (3rd October 2022) - Queiroz, Antônio C. M.; Marques, Tatianne G.; Ribas, Carla R.; Cornelissen, Tatiana G.; Nogueira, Anselmo; Schmidt, Fernando A.; Feitosa, Rodrigo M.; Sobrinho, Tathiana G.; Quinet, Yves; Baccaro, Fabrício B.; Ulysséa, Mônica A.; Vargas, André B.; et al.
Abstract: Tropical studies traditionally describe insect diversity variation throughout the year. The temporally structured responses of insect assemblages to climate seasonality vary across ecosystems due to gradients of resource availability and limiting ecological factors. These idiosyncratic responses might be particularly true across the vast geographical range of the Brazilian territory, including various environments that harbor one of the most diverse ant faunas worldwide. This study addressed the relationship between ant diversity and climatic seasonality, performing a quantitative review of the published data on ant diversity collected in Brazil. We investigated the seasonality effect on ant abundance and richness described in the literature in 47 papers published between 2000 and 2018. These studies were developed mainly in the Atlantic Forest biome and collected ants with pitfall traps on the soil/litter stratum. We initially carried out a vote‐counting procedure by comparing the number of significant results describing seasonal differences in the ant assemblage. We found that most papers described a similar pattern of ant abundance, richness, and species composition between seasons. However, when we performed a meta‐analysis, we observed a clear pattern of higher ant abundance and richness in the wet/summer season compared with the dry/winter season. Our meta‐analysis reveals that the ant diversity decreases in the dry season, strongly in the Cerrado biome. Additionally, we point out differences in the sampling effort across biomes, indicating the need for further investments in studies focused on temporal diversity patterns, including seasonal effects, on the insect assemblage in biomes less investigated so far. Abstract in Portuguese is available with online material. Abstract : This study addressed the relationship between ant diversity and climatic seasonality, performing a quantitative review of the published data on ant diversity collected in Brazil. Our meta‐analysis reveals that the ant diversity globally decreases in the dry season, strongly in the Cerrado biome. Additionally, we point out differences in the sampling effort across biomes, indicating the need for further investments in studies focused on temporal diversity patterns, including seasonal effects, on the insect assemblage in biomes less investigated so far. RESUMEN: Estudos nos Trópicos, tradicionalmente, descrevem a variação na diversidade de insetos ao longo do ano. As respostas temporais das assembleias de insetos a sazonalidade climática variam nos ecossistemas devido a gradientes de disponibilidade de recursos e fatores ecológicos limitantes. Essas respostas podem ocorrer por toda a vasta extensão geográfica do território brasileiro, incluindo vários ambientes que abrigam uma das mais diversas faunas de formigas do mundo. Este estudo abordou a relação entre diversidade de formigas e a sazonalidade climática, através de uma revisão quantitativa dos dados publicados sobre diversidade de formigas coletados no Brasil. Investigamos o efeito da sazonalidade na abundância e na riqueza de formigas descrito na literatura e obtivemos 47 trabalhos publicados entre 2000 e 2018. Esses estudos foram desenvolvidos principalmente no bioma Mata Atlântica, coletaram formigas com armadilhas Pitfall e no estrato solo/serrapilheira. Inicialmente, realizamos o procedimento de contagem de votos comparando o número de resultados significativos que descrevem diferenças sazonais na assembleia de formigas. Encontramos a maioria dos artigos descrevendo um padrão semelhante de abundância, riqueza e composição de espécies de formigas entre as estações. No entanto, quando realizamos uma meta‐análise, observamos um padrão claro de maior abundância e riqueza de formigas na estação chuvosa/verão em comparação com a estação seca/inverno. Nossa meta‐análise revela que a diversidade de formigas diminui na estação seca, especialmente no bioma Cerrado. Adicionalmente, apontamos diferenças no esforço amostral entre biomas, indicando a necessidade de mais estudos focados em padrões de diversidade temporal, incluindo efeitos sazonais, na assembleia de insetos em biomas com menor concentração de estudos.